Profitabilty and Liquidity Analysis To Asses Financial Performance Of PT. Adaro Energy Tbk. - Kusi, Ameliyani; Mahmuda, Dewi; Ridzal, Nining Asniar (Proceeding Universitas Muhammadiyah Yogyakarta Graduate Conference, 2020)
This study aims to assess the financial performanceof PT. Adaro Energy Tbkby using financial ratio analysis during 2018-2019. The financial ratios used are profitability and liquidity. Profitabilityratios of PT. Adaro Energy Tbkshows an efficient performance in terms of Net Profit Margin where the ratio is above the industry average. This great performance also shows by company’s Return On Assets where the value is also above the industry average. While in terms of Return on Equity, the company performance is not good because the ratio is below the industry average. In terms of liquidity, the company’s performance shows good liquidity because both Current Ratio and quick ratio indicatesthe condition of company liquidity is very good, where both ratios are above the industry average.